Social Marketing for Social Change. (June 2016) - Wood, Matthew
This article explores the role of social marketing in achieving health equality and social change in the context of obesity, one of the most serious global public health issues we face today. Social marketing has traditionally taken a downstream focus, targeting individuals to change their behavior. This article takes a critical perspective, supporting moves toward upstream social marketing and applying a socioecological model to social marketing theory. At the macrolevel, the marketing activities of some companies and social–economic environment mean it is difficult for some consumers to make healthy choices—for example, food and drink. At the microlevel, there is robust evidence parenting style and quality of preschool education during the critical early years' period of child development profoundly influences long-term health and life outcomes. Ecological models enable social marketers and policy makers to understand which interventions are likely to reduce inequality through sustainable, holistic positive behavior change compared with short-term, issue-based programs.